COVID-19 Influence on Place Branding in Georgia: Challenges and Opportunities - Irine BERIDZE; Gela MAMULADZE (Communications of International Proceedings, 2021)
The paper evaluates impact of the global challenge COVID-19 on the place branding of Georgia. It is analyzed which challenges, new trends, approaches and opportunities were posed by the new corona virus in place branding direction, that first appeared in 2019 in the city of Wuhan, China and spread all over the world. Has it affected on country’s image and reputation which is utterly significant for perceiving a country as an attractive investment and tourism destination, a desired place for foreigners to come to work or study, as well as for the local population. On the bases of analyzing bibliographic research and empirical materials, it is identified importance and impact of crises management on place branding development. According to the conducted survey, it is showed off those challenges and opportunities which COVID-19 arose for the place branding stakeholders of Georgia: Government, the local population, tourists and investors. Based on the opinions of experts, processed theoretical and practical materials, the data obtained as a result of the research were analyzed and found out which stakeholders were impacted mostly and why. Accordingly, there were made relevant conclusions and recommendations.
Keywords: Place Branding; Covid-19; Communication; Challenge; New Opportunities